Type II collagen from squid cartilage mediated myogenic IGF-I and irisin to activate the Ihh/PThrp and Wnt/β-catenin pathways to promote fracture healing in mice. Issue 14 (3rd June 2021) - Li, Zhuo; Tian, Yingying; Zhang, Lei; Zhang, Tianqi; Wang, Peng; Wang, Jingfeng
Abstract : Fractures are the most common large-organ, traumatic injury in humans. Abstract : Fractures are the most common large-organ, traumatic injury in humans. The fracture healing stage includes the inflammatory stage (0–5d), cartilage callus stage (5–14d) and hard callus stage (14–21d). All mice underwent open tibial fracture surgery and were treated with saline, Glu or SCII for 21d. Calluses were harvested 5d, 10d and 21d after fracture. Compared with the model group, SCII significantly decreased TNF-α and increased aggrecan serum levels by 5d. H&E results showed that fibrous calluses were already formed in the SCII group and that chondrocytes had begun to proliferate. By 10d, the chondrocytes in the SCII group became hypertrophic and mineralized, and the serum TGF-β and Col-Iα levels were significantly increased, which indicated that the mice with SCII treatment rapidly passed the cartilage repair period and new bone formation was accelerated. Skeletal muscle repaired bones through muscle paracrine factors. IGF-1 and irisin are the two major secretory cytokines. The results showed that the content of muscle homogenate IGF-1 in the SCII group reached the peak at 10d, followed by the up-regulation of Ihh, Patched, Gli1 and Col10α in the callus through the bone surface receptor IGF-1R. Besides, SCII also significantly elevated the muscle irisin level (10 and 21d), and then increased Wnt10b, LRP5, β-catenin and Runx2 expression in the callus by receptor αVβ5. These results suggest that SCII can accelerate the process of endochondral osteogenesis and promote fracture healing through activating the Ihh / PThrp and Wnt / β-catenin pathways by regulating muscle paracrine factors. To our knowledge, this is the first study to investigate the effect of marine-derived collagen on fracture healing. This study may provide a theoretical basis for the high-value application of the laryngeal cartilage of squid in the future.